Self-Amplification Mechanisms of Mast Cell Activation: A New Look in Allergy - He, S.; Zhang, H.; Zeng, X.; Yang, P. (Current Molecular Medicine, 2012)
Allergic diseases are major diseases involving approximately 22% of world population. In recent years, accumulated evidence suggests that apart from IgE, allergens may provoke immediate allergic reactions via other pathways such as IgG, toll like receptor (TLR) dependent ones. In addition, large numbers of low molecular weight molecules (LMWM) such as sphingosine-1-phosphate and iodinated contrast agents have been observed to cause allergy. Therefore, the current definition of allergy, a group of IgE mediated diseases appears difficult to cover all allergic reactions. Since even IgE dependent allergic reactions are carried out through activation of mast cells and basophils, and all allergens mentioned above can activate these cells, we hypothesize that allergic reactions are mast cell and basophil mediated inflammatory process as it is the activated mast cells and basophils that initiate the pathological process of the immediate allergic reactions, whereas IgE only serves as one of the activators of these cells.
Keywords: rhinitis